Development of an effective organic liquid manure for vegetable crops - Asha V Pillai (Department of Agronomy, College of Agriculture, 2012)
An investigation entitled “Development of an effective organic liquid manure for vegetable crops” was carried out at College of Agriculture, Vellayani during 2010–2012. The main objective of the study was to develop a safe organic phytotonic with about 2% nitrogen and to evaluate its influence on growth and yield of vegetables and to assess the economics of using liquid manures. The investigation comprises three phases viz; preparation of composite liquid manures, shelf life study and crop response study. The preliminary part of the experiment was conducted as a laboratory study. The nutrient content of organic sources along with common liquid manures like cow’s urine, vermiwash and two commercial organic liquid formulations (Nutrich–Z and Biosix) were estimated. It was observed that the highest N content of 6.18 % was registered by groundnut cake. Poultry manure had the highest P (0.90 %) and K content (2.14 %). The liquid extracts of common organic sources and vermiwash collected from portable vermicompost units prepared by mixing kitchen waste with different proportion of organic sources were also analysed for their nutrient content. In general, the N content of these extracts and vermiwsah ranged from 0.01 to 0.33%. To prepare a liquid manure with high N content, composite manures were prepared by mixing organic manures in definite proportions. The N content was maximum in the extract collected seven days after soaking of the composite manure groundnut cake + neem cake + poultry manure in 1:0.5:0.5 ratio. Based on the nutrient content, three promising liquid extracts of composite manures were selected for further study and the shelf life study was conducted after pH adjustment. The study was conducted in CRD with two replications. The results of the study indicated that the different containers and storage methods could not increase the shelf life of the liquid manures due to foul smell and mould growth. To improve the shelf life, these manures were subjected to autoclaving after pH adjustment and another laboratory study was conducted in CRD with three replications. The results of the study indicated that the nutrient content of